Correlation between serum proinsulin levels and fatty liver: The Dynamics of Lifestyle and Neighborhood Community on Health Study. Issue 4 (1st March 2020) - Miya, Aika; Nakamura, Akinobu; Miyoshi, Hideaki; Ukawa, Shigekazu; Nakamura, Koshi; Nakagawa, Takafumi; Terauchi, Yasuo; Tamakoshi, Akiko; Atsumi, Tatsuya
Abstract: Aims/Introduction: We explored the association between fatty liver and pancreatic β‐cell dysfunction in a general population. Materials and Methods: This cross‐sectional study included 489 (53.8% women) community‐dwelling Japanese adults. The extent of fatty liver was estimated using the fatty liver index (FLI). After all participants were divided into three groups – low (FLI <30), moderate (30 ≤FLI <60) or high (FLI ≥ 60) degree of fatty liver – serum proinsulin levels transformed into natural logarithms were compared among the three groups. To determine whether obesity modified the association of interest, the participants were stratified into two groups according to the median body mass index. Next, to determine whether hyperinsulinemia modified the association of interest, a similar stratified analysis was carried out using the median serum insulin level. Results: Logarithm (proinsulin) was significantly higher in the high FLI group than in the moderate and low groups, and it was significantly higher in the moderate group than in the low group after adjustment for age and sex ( P < 0.05). Logarithm (proinsulin) was significantly higher in the high FLI group than in the low FLI group, regardless of body mass index, after adjustment for age and sex. A similar pattern was observed regardless of serum insulin levels. Conclusions: The degree of fatty liver was positively associated with proinsulin level, regardless of the presence of obesity or hyperinsulinemia, suggesting that fatty liver reflects pancreatic β‐cell dysfunction. Abstract : The degree of fatty liver was positively associated with proinsulin level. This association was observed regardless of obesity or hyperinsulinemia. The degree of fatty liver might reflect β‐cell dysfunction.